Retrograde and oscillatory shear increase across the menopause transition - Somani, Yasina B; Moore, David J; Kim, Danielle Jin-Kwang; Gonzales, Joaquin U; Barlow, Matthew A; Elavsky, Steriani; Proctor, David N (Physiological reports, 2019)
Declines in endothelial function can take place rapidly across the menopause transition, placing women at heightened risk for atherosclerosis. Disturbed patterns of conduit artery shear, characterized by greater oscillatory and retrograde shear, are associated with endothelial dysfunction but have yet to be described across menopause. Healthy women, who were not on hormone therapy or contraceptives, were classified into early perimenopausal, late perimenopausal, and early postmenopausal stage. Resting antegrade, retrograde, and oscillatory shear were calculated from blood velocity and diameter measured in the brachial and common femoral artery using Doppler ultrasound. Serum was collected for measurements of estradiol, follicle-stimulating hormone (FSH), and luteinizing hormone. After adjusting for age, brachial artery oscillatory shear was significantly higher in early postmenopausal women (n = 15, 0.17 ± 0.08 a.u.) than both early (n = 12, 0.08 ± 0.05 a.u., P < 0.05) and late (n = 8, 0.08 ± 0.04 a.u) perimenopausal women, and retrograde shear was significantly greater in early postmenopausal versus early perimenopausal women (-19.47 ± 12.97 vs. -9.62 ± 6.11 sec-1 , both P < 0.05). Femoral artery oscillatory and retrograde shear were greater, respectively, in early postmenopausal women (n = 15, 0.19 ± 0.08 a.u.; -13.57 ± 5.82 sec-1 ) than early perimenopausal women (n = 14, 0.11 ± 0.08 a.u.; -8.13 ± 4.43 sec-1 , P < 0.05). Further, Pearson correlation analyses revealed significant associations between FSH and both retrograde and oscillatory shear, respectively, in the brachial (r = -0.40, P = 0.03; r = 0.43, P = 0.02) and common femoral artery (r = -0.45, P = 0.01; r = 0.56, P = 0.001). These results suggest menopause, and its associated changes in reproductive hormones, adversely influences conduit arterial shear rate patterns to greater oscillatory and retrograde shear rates.
Keywords: menopauza; Menopause; reologie krve; Luteinizing Hormone; retrograde shear; Endothelium, Vascular; arterie; Middle Aged; Hemorheology; Adult; luteinizační hormon; Menopause transition; ženské pohlaví; Humans; Follicle Stimulating Hormone; Estradiol; folikuly stimulující hormon; lidé středního věku; cévní endotel; oscillatory shear; dospělí; Female; estradiol; Arteries; lidé